2019
DOI: 10.1101/631309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual difference in serial dependence results from opposite influences of perceptual choices and motor responses

Abstract: 1

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Similar ideas are now emerging in related fields, such as serial dependence of orientation perception (e.g. Gekas, McDermott, & Mamassian, ; Zhang & Alais, ).…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Similar ideas are now emerging in related fields, such as serial dependence of orientation perception (e.g. Gekas, McDermott, & Mamassian, ; Zhang & Alais, ).…”
Section: Introductionsupporting
confidence: 55%
“…We took this approach to avoid making the task too difficult for participants and to make analysis of the bias itself simpler, though other studies have used random response mappings between trials (e.g. Pape et al., ; Zhang & Alais, ).…”
Section: Experiments 2—methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we found response was key in forming positive serial dependence, it may be not due to the motor system per se. In fact, there are studies showing that motor responses show repulsive serial dependence, that is, a tendency of alternating motor responses between trials (Pape et al, 2017;Pape & Siegel, 2016;Zhang & Alais, 2020). It is possible that the positive serial dependence is the characteristic of working memory in stabilizing representations of the outside world by integrating information over time (Kiyonaga et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is possible that the requirement of making responses helps transfer sensory information into working memory and strengthens the storage of rates in working memory, hence biasing the subsequent rates reproduction. The overall serial dependence may be the weighted average across these serial effects at each stage (Zhang & Alais, 2020), which could be the reason why previous studies found mixed results of serial dependence being repulsive or positive.…”
Section: Discussionmentioning
confidence: 99%